The Relationship between the Severity of Restless Legs Syndrome and Demographic Characteristics of Hemodialysis Patients - Zhamis, Samaa Ali; Abed, Rajaa Ibrahim (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): To find out the relationship between the patients’ severity of restless legs syndrome and their demographic characteristics (age, gender, marital status, occupation, monthly income, and education level).Methods: A cross-sectional study design was conducted on a purposive sample of 90 hemodialysis patients diagnosed with restless legs syndrome in the Wasit and Thi-Qar hemodialysis centers. The study started on October 10th, 2022, to May 31st, 2023. 12 panelists confirmed the content validity of the scale, while Cronbach's alpha of (0.78) confirmed the scale reliability. Data were analyzed using descriptive statistical data analysis that is frequency and percentage, in addition to inferential statistical data analysis are Pearson correlation, independent t-test, and analysis of variance (ANOVA).Results: The study findings show there is a statistically significant relationship between the severity of restless legs syndrome and gender (P-value = 0.033), while no other statistically significant relationship was found among patients’ age, marital status, occupation, monthly income, or level of education and the severity of restless legs syndrome (P-value >0.05).Conclusions: The study concluded that there is a statistically significant relationship between gender and hemodialysis patients' severity of restless legs syndrome; however, no other statistically significant relationship was found among patients' age, marital status, occupation, monthly income, or level of education with the severity of restless legs syndrome.Recommendations: The study recommends that future studies focus on the severity of restless legs syndrome among hemodialysis patients with a larger sample size and in more hemodialysis centers in Iraq.